Risk Factors Associated with The Incidence of Malaria in Mimika Baru District - Batrisyia, Dayini; Herbawani, Chahya Kharin; Buntara, Arga; Hanifah, Laily (Poltekkes Kemenkes Jakarta III, 2025)
Malaria remains a major health issue in Indonesia, particularly in the eastern regions, which contribute to about 90% of national cases. Mimika Regency, especially Mimika Baru District, is one of the high-endemic areas. This study aimed to identify human and environmental risk factors associated with malaria incidence. The research, conducted from May to June 2025 in Mimika Baru District, used a cross-sectional design with 155 respondents selected through stratified random sampling. Data were analyzed univariately and bivariately using the chi-square test. Variables included age, gender, education, occupation, healthcare access, knowledge, ventilation screen use, mosquito net use, ceiling availability, and the existence of mosquito breeding sites, resting places, and animal shelters. Results showed that 83.6% of respondents had contracted malaria in the past year. Factors significantly associated with malaria incidence were the use of ventilation screens (p=0.050), mosquito nets (p=0.025), ceilings (p=0.015), breeding sites (p=0.002), resting places (p=0.015), and animal shelters (p=0.025). Strengthening malaria prevention and control through public education, distribution of insecticide-treated nets, and improved environmental management is recommended.